Hubungan Estetika Senyum dengan Persepsi Diri pada Mahasiswa Fakultas Kedokteran Gigi - Puspitasari, Yustisia; Novawaty, Eva; Aslan, Sarahfin; Arifin, Nur F.; Septiriani, Andi Azisa D. (e-GiGi, 2025)
Abstract: As the field of orthodontics develops progressively, many patients undergo orthodontic treatment to improve their dentofacial characteristics, which support the facial appearance and aesthetics of their smile. An individual who has unesthetic smile and tooth arrangement is considered to lack self-confidence and have a negative effect, especially on his/her social relationship, education, and career. This study aimed to determine the relationship between smile aesthetics and self-perception. This was a descriptive and analytical study with a purposive sampling design. Samples were students of Faculty of Dentistry Universitas Muslim Indonesia. The relationships between intercommisural distance at midline (mm) and self-perception, and between intercommisural distance (mm) and self-perception were tested using the Pearson correlation test. The results showed that based on the Pearson test, the relationship between intervermillion distance in the midline (mm) and self-perception had a p-value of 0.708, meanwhile the relationship between intercommission distance (mm) and self-perception had a p-value of 0.815. In conclusion, there is no significant relationship between smile aesthetics and self-perception among students of the Faculty of Dentistry, Universitas Muslim Indonesia. Keywords: smile aesthetics; self-perception    Abstrak: Seiring dengan perkembangan dan kemajuan dalam bidang ortodonti, banyak pasien yang melakukan perawatan ortodonti untuk meningkatkan karakteristik dentofasial yang mendukung penampilan wajah dan estetika senyum. Seseorang yang memiliki senyum dan susunan gigi kurang estetik dianggap kurang percaya diri dan dinilai memiliki efek negatif terutama terhadap hubungan sosial, pendidikan, dan karir. Penelitian ini bertujuan untuk mengetahui hubungan estetika senyum dengan persepsi diri. Jenis penelitian ialah deskriptif analitik dengan desain purposive sampling. Sampel penelitian ialah mahasiswa Fakultas Kedokteran Gigi Universitas Muslim Indonesia. Hubungan antara variabel intervermillion distance at midline (mm) dengan persepsi diri, serta antara variabel intercommissural distance (mm) dengan persepsi diri diuji menggunakan uji korelasi Pearson. Hasil uji Pearson mendapatkan nilai p=0,708 untuk hubungan antara intervermillion distance at midline (mm) dengan persepsi diri serta nilai p=0,815 untuk hubungan antara intercommissural distance dengan persepsi diri. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara estetika senyum dengan persepsi diri mahasiswa Fakultas Kedokteran Gigi Universitas Muslim Indonesia Kata kunci: estetika senyum; persepsi diri